2022
DOI: 10.1093/infdis/jiac017
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Autoimmune Activation and Proinflammatory State in Post-Coronavirus Disease 2019 Syndrome

Abstract: Background The immunopathological pathways enabling post-COVID syndrome (PCS) development are not entirely known. We underwent a longitudinal analysis of patients with COVID-19 who developed PCS aiming to evaluate the autoimmune and immunological status associated with this condition. Methods Thirty-three patients were included for longitudinal clinical and autoantibody analyses of whom 12 patients were assessed for cytokines… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
93
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 33 publications
4
93
0
4
Order By: Relevance
“…The specific processes behind its emergence and the impact of biological changes on clinical phenotypes remain poorly understood. Patients with PCS may exhibit persistence of inflammation and predominance of an immune effector phenotype after recovery [ 1 ].…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations
“…The specific processes behind its emergence and the impact of biological changes on clinical phenotypes remain poorly understood. Patients with PCS may exhibit persistence of inflammation and predominance of an immune effector phenotype after recovery [ 1 ].…”
Section: Commentarymentioning
confidence: 99%
“…In addition, anti-IFN antibodies are implicated in mortality and correlate with age [ 4 ]. Autoantibodies may persist after COVID-19, and latent PolyA increases over time in PCS [ 1 ]. In a recent study by Liu et al [ 5 ], the authors observed that SARS-CoV-2 infection, even in the absence of severe clinical disease, can cause a broad autoantibody response exhibiting sex-specific patterns of prevalence and antigen specificity.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…The causes and mechanisms underlying post-COVID syndrome are still to be investigated. Several current hypotheses include chronic self-maintaining inflammation, immune system and redox imbalance, an autoimmune phenomenon, and a hormonal component [ 67 , 68 ]. In the present clinical study we attempted to evaluate the effects of FFS on some of these mechanisms: functions of circulating phagocytes PMN crucial for the defence from secondary infections and a source of self-maintaining inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Protection against oxidative stress in COVID-19 and post-COVID patients is essential because imbalance of normal redox status to the oxidative millie seems to be one of the major causes of post-COVID syndrome [ 5 , 67 , 68 ]. According to our data, overproduction of highly oxidising agents nitrites/nitrates and their presence in plasma is a characteristic feature of post-severe-COVID period ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%